Solitary fibrous tumour of the submandibular region: a rare entity - Ishak, Noor Liza; Sabir Husin Athar, Primuharsa Putra; Md Pauzi, Suria Hayati; Mohamed Rose, Isa; Mohamad Yunus, Mohd Razif (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Solitary fibrous tumours of the head and neck region are extremely rare. The clinical diagnosis is often difficult to establish, and this lesion may be indistinguishable from other soft tissue neoplasms. An 18-year old Chinese gentleman presented with a painless right submandibular swelling which was increasing in size for eight months. A computed tomography scan showed a well-defined solid mass measuring about 2.0 x 2.96 cm in the submandibular region. The tumour was resected and was confined within its capsule. Immunohistochemical staining was strongly positive for CD34, CD 99, and vimentin and negative for desmin, smooth muscle actin (SMA), cytokeratin, S100 and CD68. The microscopic and immunohistochemical profile were compatible with solitary fibrous tumour. Distinguishing solitary fibrous tumours from various spindle neoplasms can be difficult. In view of the resemblance, immunohistochemical staining can help differentiate solitary fibrous tumour from spindle neoplasm.